2007
DOI: 10.1016/j.topol.2007.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Heegaard splittings of toroidal 3-manifolds

Abstract: We show that after one stabilization, a strongly irreducible Heegaard splitting of suitably large genus of a graph manifold is isotopic to an amalgamation along a modified version of the system of canonical tori in the JSJ decomposition. As a corollary, two strongly irreducible Heegaard splittings of a graph manifold of suitably large genus are isotopic after at most one stabilization of the higher genus splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Rubinstein and Scharlemann have shown that if M is non-Haken, then two Heegaard splittings of M of genus g and g 0 , respectively, with g g 0 are isotopic after at most 7g C 5g 0 9 stabilizations of the larger genus splitting [19]. In previous work [7], the author showed that under mild assumptions, two Heegaard splittings of genus g obtained by Dehn twisting along a JSJ torus in M are isotopic after at most 4g 4 stabilizations. In neither case have these bounds been shown to be sharp.…”
Section: Stabilizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Rubinstein and Scharlemann have shown that if M is non-Haken, then two Heegaard splittings of M of genus g and g 0 , respectively, with g g 0 are isotopic after at most 7g C 5g 0 9 stabilizations of the larger genus splitting [19]. In previous work [7], the author showed that under mild assumptions, two Heegaard splittings of genus g obtained by Dehn twisting along a JSJ torus in M are isotopic after at most 4g 4 stabilizations. In neither case have these bounds been shown to be sharp.…”
Section: Stabilizationmentioning
confidence: 99%
“…This is called the Stabilization Problem. Several examples are known where only one stabilization (of the larger genus splitting) is needed to achieve isotopy (see eg Derby-Talbot [6], Hagiwara [8], Schultens [23] and Sedgwick [25]). Recently, Bachman [2] and independently Hass, Thompson and Thurston [10] as well as Johnson [13; 14] have shown that the necessary number of stabilizations can be much greater than one, in fact as large as g , where g denotes the genera of the initial Heegaard splittings.…”
Section: Stabilizationmentioning
confidence: 99%
See 3 more Smart Citations